THE EFFECT OF GREEN BANKING ON COMPANY VALUE IN THE INFOBANK 15 INDEX PERIOD 2020-2023 - Dwiningsih, Sri; Purwantoro, Handik; Riswanto (Sekolah tinggi ilmu ekonomi pemuda, 2024)
The aim of the author in conducting this research is to determine the effect of green banking on company value in the 15th Infobank Index for the 2020-2023 period. The method used by the author in conducting this research is descriptive analysis method and simple regression analysis. Data processing was carried out using IBM SPSS STATISIC 25. The population of this study was all companies in the INFOBANK 15 Index for the 2020-2023 period with the number of samples taken according to the researcher's criteria of 11 companies. Partial test results show that Green Banking has a positive and significant effect on company value on the INFOBANK 15 Index. This means that the higher the Green Banking contribution, the higher the company value on the INFOBANK 15 Index. The magnitude of the influence of Green Banking is 0.216 or equivalent to 21.6% in a positive direction, which means that if the Green Banking variable increases by 1%, the company value will increase by 21.6%.